CEDAW implementation in Malaysia: an overview of reservations from Islamic perspective - Ahmad, Nadzrah; Aminudin, Rabi'ah; Othman, Roslina; Ghazali, Norzulaili; Ismail, Nurul Syuhada (IIUM Press, International islamic University Malaysia, 2017)
This study examines the extent to which CEDAW has beenimplemented in Muslim countries particularly in Malaysia. Applying aqualitative approach comprising of content and comparative analyses, thepaper seeks to understand the reservations Muslim countries have concerningthe compatibility of CEDAW’s understanding of gender equality withthe SharÊÑah’s perspective on gender and gender relations. It does this byexamining Malaysia’s implementation of CEDAW in three areas: constitution,legal and policy based on the SharÊÑah, and CEDAW’s articles. By doing so,the paper clarifies misconceptions regarding the SharÊÑah’s treatment of genderrelated issues. This paper will also explore the different roles given to eachgender and how they are positioned in the overall worldview of Islam. Thepaper concludes that both the SharÊÑah and CEDAW share the same positiveadvocacy of gender equality albeit with different approaches. The differencesin approach should be respected as they underscore deep and complex creedaland social commitments that define the different countries with their uniquecultural settings.